'My desire to play was stronger than my fear of re-injury': athlete perspectives of psychological readiness to return to soccer following anterior cruciate ligament reconstruction surgery. Issue 3 (26th May 2020) - Kunnen, Mitchell; Dionigi, Rylee A.; Litchfield, Chelsea; Moreland, Ashleigh
ABSTRACT: The aims of this qualitative study were to understand how athletes (a) defined psychological readiness and (b) knew when they were ready to return to soccer following anterior cruciate ligament (ACL) reconstruction surgery. Data were collected from a group of 21 (male and female) athletes who had undergone ACL reconstruction surgery and returned to playing soccer. An open-ended, in-depth online survey was created to gather data on athlete understandings of psychological readiness, their experiences of overcoming psychological barriers when returning to sport, and any emotions or complications associated with their return to sport. Two main themes were uncovered in this study: 'Having Confidence' and 'Love of the Game'. This research offers a greater understanding of how psychological readiness is defined from the perspective of soccer players, (particularly those returning to lower levels of competition, such as local and regional amateur clubs), than has been found in previous research.